PENGARUH KEBIASAAN MEROKOK TERHADAP KEJADIAN HIPERTENSI DI RUMAH SAKIT MELATI PERBAUNGAN - BRAWA TAMA UNSANDY; SUHARTOMI . (JURNAL ILMIAH MAKSITEK, 2022)
Based on the 2018 Basic Health Research (RISKESDAS), the prevalence of hypertension based on a doctor diagnosis is8.4%. Meanwhile, based on the results of direct measurements of the population aged over 18 years, the prevalence ofhypertension is 34.1%. Therefore, it become important to identify modifiable risk factors. One of them is smoking habit.The purpose of this study was to determine the relationship between smoking and hypertension among inpatients at theInternal Medicine Outpatient Clinic of Melati Perbaungan Hospital in 2020. This study used a cross-sectional design with astudy population of all male patients at the Outpatient Clinic. Fifty-two people were taken from the population by consecutivemethods. All data were then analyzed by SPSS 25 with univariate analysis and bivariate analysis (with chi square test).From this study, it was found that there was a statistically significant relationship between smoking habits (p=0.002), type ofcigarette (p=0.008), length of smoking (p=0.014), and smoking frequency (p=0.011) against hypertension. The activesmoking behavior (OR: 7.20 95% CI: 1.89-27.50), non-filtered cigarette type (OR: 10.80; 95% CI: 1.69-68.94), smokingduration > 20 years (OR: 13.50; 95% CI: 2.15 – 84.69), and the smoking frequency of 1-9 cigarettes/day (OR: 13.50; 95%CI: 2.15-84.69) increased risk of developing hypertension. Hence, it can be concluded that there was a relationship betweensmoking and the develop of hypertension.